The Role of Continuous Assessment Learning Activities (CALA) in Enhancing Mathematics Competency and Proficiency in Secondary School Learners - Chipo Makamure; Zingiswa M Jojo (MEJ (Mathematics Education Journal), 2023)
This paper examines the significance and contribution of CALA to the mathematics knowledge of students. It focuses on the instruments and methods used in CALA to teach mathematics effectively in Zimbabwe. Learners’ failure to implement what they learn in mathematics has been worrisome to the Ministry of Education whose focus is to promote industrialisation through effective teaching and learning of STEM subjects. It is believed that most learners memorise mathematics with little understanding in order to pass an examination. Inappropriate and ill-suited assessment methods of mathematics are regarded as the principal causes of this rote learning approach by learners. The educational policy makers came up with the concept of CALA, which was effected in 2021, to all levels of education in Zimbabwe. According to the curriculum framework, learners are expected to demonstrate their knowledge of mathematics through CALA.  However, whilst the intended goal of CALA is prudent, the concern is whether teachers are knowledgeable about how this model of assessment can be implemented effectively. Ten secondary school mathematics teachers were interviewed to examine their views and practices in the classroom implementation of the CALA component. In this study, the findings established that the incorporation of the component in the teaching and learning of mathematics has come with limited benefits that were marred by teachers’ knowledge deficiency to operationalise CALA. This study recommends thorough support and developmental programmes which can equip teachers with the appropriate skills to implement CALA.